2014
DOI: 10.1080/14786419.2013.879304
|View full text |Cite
|
Sign up to set email alerts
|

Activity-guided isolation of antioxidants from the leaves ofTerminalia arjuna

Abstract: An activity-guided isolation and purification process was used to identify the l,l-diphenyl-2-picrylhydrazyl (DPPH) free radical-scavenging components of the food plant (Terminalia arjuna) of Antheraea mylitta. Dry leaves of T. arjuna were extracted with different solvents and tested for their antioxidant activity against DPPH(•). The acetone-water (8:2) extract expressed strong DPPH radical-scavenging activity, and was subjected to column chromatography over silica gel. Gallic acid, apigenin, luteolin, querce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…This variation in TPC and TFC clearly indicate that the environmental factors have some effect on the phytochemical content of the same plant in different location as also shown by studies of Bhakta and Ganjewala on Lantana camara 37 and Fonseca et al 38 . Ambika and Chauhan 44 found that gallic acid, apigenin, luteolin, quercetin, epicatechin, ellagic acid and 1-O-β-galloyl glucose were the major phenolics compounds which are responsible for the antioxidant potential of leaves extract of T. arjuna .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This variation in TPC and TFC clearly indicate that the environmental factors have some effect on the phytochemical content of the same plant in different location as also shown by studies of Bhakta and Ganjewala on Lantana camara 37 and Fonseca et al 38 . Ambika and Chauhan 44 found that gallic acid, apigenin, luteolin, quercetin, epicatechin, ellagic acid and 1-O-β-galloyl glucose were the major phenolics compounds which are responsible for the antioxidant potential of leaves extract of T. arjuna .…”
Section: Resultsmentioning
confidence: 99%
“… 41 , 42 Phenolic content present in the plants are directly correlated with their antioxidant properties. 43 Ambika et al 44 found that gallic acid, apigenin, luteolin, quercetin, epicatechin, ellagic acid and 1-O-β-galloyl glucose were the major phenolics compounds which are responsible for the antioxidant potential of leaves extract of T. arjuna. In the present study, antimicrobial activity antioxidant activity of different solvent extracts was compared in leaves and bark.…”
Section: Discussionmentioning
confidence: 99%
“…The ellagic and gallic acids derivatives, which present in ExCA, have a direct action in the capture of free radicals [ 18 ] and, in addition, are capable of stimulating the activity of the antioxidant enzymes, superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) [ 19 , 20 ], contributing to the antioxidant actions observed. The action of the ExCA in the capture of free radicals was demonstrated in this study and its possible action on antioxidant enzymes may be evaluated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that phenolic compounds are one of the most important classes of secondary metabolites of plants that display the capacity for free radical scavenging [ 10 , 82 ]. Therefore, the main bioactive compounds found in ExCA, such as ellagic and gallic acid [ 37 ], display the capacity to capture free radicals and may also stimulate the activity of the antioxidant enzymes, such as superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) [ 83 ], together with the attenuation of diabetic cardiomyopathy in mice [ 84 ].…”
Section: Common Brazilian Cerrado Campomanesia mentioning
confidence: 99%